Comparative Study of Catalytic Hydrogenation of 9-Ethylcarbazole for Hydrogen Storage over Noble Metal Surfaces - Eblagon, K; Tam, K; Yu, K; Tsang, S (2012)
The use of liquid organic hydrides (LOH) as a chemical hydrogen store to supply hydrogen gas for a polymer electrolyte membrane fuel cell (PEFC) is explored. In the present work, hydrogenation of 9-ethylcarbazole is particularly investigated in the liquid phase over different unsupported noble metal powders. The kinetics obtained from the hydrogenation of the substrate over these catalytic systems are modeled, and the derived fundamental rate constants are systematically compared. It is found that the differences in activity and product distribution of the reaction over different metal surfaces depend critically on the electronic structures of the metals. From the prospective application of 9-ethyl-carbazole, an effective catalyst should be able to convert the substrate to the fully hydrogenated cis product without forming any kinetically stable intermediates. Ruthenium is the most active catalyst among all the metals studied for this reaction. However, this catalyst suffers from relatively low selectivity with the accumulation of large quantities of partially hydrogenated intermediates due to weak adsorption and poor surface diffusion of the intermediates for further hydrogenation. © 2012 American Chemical Society.